Impact of intercultural communicative competence on cultural identity education - Ruiz, Nora (2022)
Preservation of cultural identity is a recurring concern due to the accelerated loss of cultural elements such as the original language, customs, and oral traditions. Especially in the new generations that show indifference, as a consequence of the displacement of their places of origin and the discrimination expressed by culturally predominant groups. This study aimed to review articles and analyze the contributions of intercultural communicative competence. The documentary review methodology of 50 articles published in reliable databases was used. Conceptual definitions, characteristics, components, elements, principles, and dimensions were considered. Concluding that it is necessary to intervene in the schools with strategies to mitigate the predominance of cultural homogenization and, consequently, the loss of the cultural identity of minority groups.